Modeling the Environmental Impact of Aquacultural Facilities - A Foundation for Future Management - Dale M. Licata (Modeling, Identification and Control, 1986)
A numerical model for computing the oxygen consumption and leakage of nutrients and organic matter from an aquacultural facility has been implemented. It is based upon the energy equation for fish and accounts for metabolism and growth over a range of temperatures and fish weight classes.